Schools: wrong spaces face the ones desired by the students - Alonso Sanz, Amparo (2017)
This work examines the ideas that some students have about improving their space, projections of desires that children have toward their own school. This study about the aesthetic quality it's developed thanks to the participation of three primary schools in Alicante city, Spain. The methodology combines Visual Arts Based Educational Research and Image Based Research to obtain by graphical methods the visual voice of children. The results are different drawings and collages rich in information and in communication contents, which are analysed qualitatively and quantitatively. We conclude with the aesthetics of the desired educational environments. The space is defined as fresh and natural; designed for both recreational activity and learning, as for rest and affective interpersonal relationships; attractive, cozy, comfortable and homely; permeable to the outside rural or urban environment; and with a creative external appearance. It is found that the demands of students do not always coincide with the answers given by adults. We point the urgent need of hearing the voice of all those involved in the process of teaching and learning.